The Community House (Dom Ludowy) in Nałęczów as an example of social architecture of the early 20th century - Boguszewska, Kamila Lucyna (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
One of the most interesting facilities which were supposed to improve the quality of education of the poorest social strata were community houses. The popularity of this kind of institutions, dating back to the end of the 19th century and the first half of the 20th century, resulted in the construction of the Community House in Nałęczów, which, based on best practices, was to be a model of the realisation of a new, progressive society. The article presents the principles and "rules" for establishing such facilities by local communities in the context of activities undertaken in the difficult social and political situation of the areas under Russian rule. The history, operating principles, and architecture of the Community House in Nałęczów, which is an example of an out-of-the-box facility maintained in the national style, were herein analysed.